2016
DOI: 10.5751/es-08353-210222
|View full text |Cite
|
Sign up to set email alerts
|

Culturally significant fisheries: keystones for management of freshwater social-ecological systems

Abstract: ABSTRACT. Indigenous peoples of North America, Australia, and New Zealand have a long tradition of harvesting freshwater animals. Over generations of reliance and subsistence harvesting, Indigenous peoples have acquired a profound understanding of these freshwater animals and ecosystems that have become embedded within their cultural identity. We have identified trans-Pacific parallels in the cultural significance of several freshwater animal groups, such as eels, other finfish, bivalves, and crayfish, to Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 53 publications
1
68
0
Order By: Relevance
“…Community engagement during the design and development of conservation and management approaches has tended to focus on issues and views from stakeholders who derive extractive (harvest) or non‐extractive (tourism) economic value from the species (Hesselink, Goldstein, van Kempen, Garnett, & Dela, ; MEA, ; Todd et al, ; United Nations Environment Programme (UNEP), ). An emerging body of literature has uncovered how aquatic species support complex cultural relationships and non‐economic values across different sectors of society, fitting the definition of a CKS (Cristancho & Vining, ; Garibaldi & Turner, ; Noble et al, ), the present study showed that E. armatus is an important part of the cultural identity of stakeholders across the MDB, who view the species as a social–ecological keystone. Aboriginal Traditional Owners consider E. armatus to be a CKS by supporting subsistence harvests, ceremonies, totemic beliefs (e.g.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Community engagement during the design and development of conservation and management approaches has tended to focus on issues and views from stakeholders who derive extractive (harvest) or non‐extractive (tourism) economic value from the species (Hesselink, Goldstein, van Kempen, Garnett, & Dela, ; MEA, ; Todd et al, ; United Nations Environment Programme (UNEP), ). An emerging body of literature has uncovered how aquatic species support complex cultural relationships and non‐economic values across different sectors of society, fitting the definition of a CKS (Cristancho & Vining, ; Garibaldi & Turner, ; Noble et al, ), the present study showed that E. armatus is an important part of the cultural identity of stakeholders across the MDB, who view the species as a social–ecological keystone. Aboriginal Traditional Owners consider E. armatus to be a CKS by supporting subsistence harvests, ceremonies, totemic beliefs (e.g.…”
Section: Discussionsupporting
confidence: 61%
“…Harvesting a threatened species is often a complex issue because these species often support cultural connections for First Nations Peoples. Aboriginal People are often adversely affected by top‐down government policies that fail to understand the importance of traditional access to a biological resource (Noble et al, ; Schnierer & Egan, ; Smyth, Isherwood, & Schnierer, ). For instance, Aboriginal communities still rely on E. armatus as an important subsistence and cultural food source in parts of New South Wales, where populations are still found in moderate numbers (S. Schnierer, pers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, there is little evidence that symbolic values depend on the presence of the species in our case. Nevertheless, we argue that it is important to safeguard symbolic species and related cultural values to manage successfully social-ecological systems on the long-term (Noble et al 2016). Symbolic species are emotionally significant to many Alpine residents, but they may be vulnerable to global change and their extinction may affect their symbolic meaning.…”
Section: Maintenance Of Symbolic Species and Associated Valuesmentioning
confidence: 92%